FORENSIC CHALLENGES AND TECHNIQUES IN CLOUD COMPUTING ENVIRONMENTS: A SYSTEMATIC LITERATURE REVIEW - Dr. Muhammad Tanveer; Nabeel Ali Khan; Majid Ali; Rutab Islam; Mujeeb Sattar; Muhammad Shoaib (Spectrum of Engineering Sciences, 2025)
The use of cloud computing has transformed the management of data, providing scalability and cost-effectiveness. Yet, it poses serious forensic issues, such as data volatility, multi-tenancy, Legal barriers, and encryption challenges, that affect the acquisition, retention, and examination of digital evidence. This systematic literature review (SLR) analyzes these issues and reviews methods to mitigate them, providing an in-depth overview of the discipline. Based on 52 high-quality research articles from reputable journals and conferences, the research organizes forensic issues across cloud service models (IaaS, PaaS, SaaS) and evaluates tools such as blockchain for ensuring evidence integrity, AI-based analysis for handling large data volumes, and tenant isolation frameworks for multi-tenant settings. It points out the effects of cloud systems' dynamic and distributed nature on handling evidence and the essential role of cloud service providers in forensic preparedness. This review establishes gaps in existing methodologies, suggests quality assessment criteria, and maps out future research avenues. It offers insightful recommendations for researchers, practitioners, and policymakers seeking to develop forensic capabilities in cloud settings while countering legal, technical, and procedural complexities.